Effectiveness of Acupressure on Emesis Gravidarum in the First Trimester Pregnant Women: Efektivitas Akupresur Terhadap Mual dan Muntah pada Ibu Hamil Trimester Pertama - Indah, Indah Elizabeth; Dinengsih, Sri; Kundaryanti, Rini (Jurnal Kebidanan Midwiferia, 2023)
Emesis gravidarum is nausea and vomiting that can cause dehydration and drastic weight loss that occurs in the first trimester of pregnancy. Acupressure on PC point 6 serves to control the function of the cerebral cortex through the nervous system that inhibits or reduces the nausea vomiting response. Objective: This study was to determine the effectiveness of acupressure on vomiting in first trimester pregnant women at the Karanggan Medika Clinic Gungung Putri Bogor in 2023. Research Methods: This study used a quasi-experiment design with pre test and post test design with control group. Sampling using purposive sampling technique with 28 respondents. The instrument used was Pregnancy-Unique Quantification of Emesis and Nausea (PUQE)-24 assessing the level of emesis gravidarum with scores ≤6 to ≥13. Results: Based on the results of non-parametric statistical analysis, namely by using the Mann Whitney test, the P-value is 0,001 (0,05) which means that there is a significant difference in first trimester pregnant women who are given the intervention with those who are not given the intervention. And the results of the Wilcoxon test P-value 0,001 (0,05), namely there is an effect of giving acupressure to emesis gravidarum in first trimester pregnant women at the Karanggan Medika Clinic Gunung Putri Bogor in 2023. Suggestion: It is expected for first trimester pregnant women who experience emesis gravidarum to apply acupressure as a therapy that can overcome nausea and vomiting during first trimester pregnancy.